PRODUKTIVITAS TERNAK BABI YANG DIPELIHARA SECARA TRADISIONAL DI DESA TAWIRI KECAMATAN TELUK AMBON - Renny Debora Woriun; Godlief Joseph; Abraham H. Tulalesy (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
The objective of this study was to analyze the productivity of traditionally raised pigs in Tawiri Village, Teluk Ambon District, Ambon City. The measured parameters included respondent characteristics—such as age, gender, education level, farming experience, number of pigs owned, rearing system, and occupation—as well as pig productivity, which consisted of litter size and birth weight. This research employed a descriptive method involving 15 pig farmers as respondents. The results showed that most of the farmers were male (60%), within the productive age range, generally had a high school education, and had 5–10 years of experience in pig farming. It was also found that the majority of farmers owned more than six pigs, applied a semi-intensive rearing system, and practiced mixed farming. The productivity of traditionally raised pigs in Tawiri Village was considered fairly good, although there is still room for improvement. The average litter size ranged from 7 to 9 piglets, with an average birth weight of 1.0 kg. The study recommends optimizing genetic potential through improved feed and sow management, especially during the gestation period.